Ofloxacin induced hypersensitivity reaction - Ramineni, Hari Babu; Eluri, Pravallika; Vipparla, Kumudini; Suryadevara, Vidyadahara (International Journal of Research in Medical Sciences, 2017)
Ofloxacin is a commonly used antimicrobial agent to combat various infections. The adverse profile of quinolones includes gastrointestinal symptoms, which are the most frequent, neuropsychiatric symptoms, hematologic abnormalities are less common. We report a rare case of ofloxacin induced hypersensitivity reaction in a 57 year old female patient with complaints of rashes over the axilla, upper limb and back, abdomen, thorax associated with exfoliation of skin all over the axilla associated with severe itching. Based on history and clinical examination patient was diagnosed as ofloxacin induced hypersensitivity reaction and was successfully treated with antihistamines and corticosteroids. Pharmacovigilance should be a part of patient care in order to reduce occurrence of adverse drug reaction and also encourage practitioners in reporting so as to gather more and more data regarding adverse drug reactions.